Analysis of students' positive emotions around the green space in the university campus during the COVID-19 pandemic in China - Liu, Shaobo; Ji, Yifeng; Li, Jiang; Peng, You; Li, Zhitao; Lai, Wenbo; Feng, Tao (Frontiers in Public Health, 2022)
Green space in university campus is of paramount importance to students’ emotional and psychological restoration. Students’ positive emotion can be aroused when immersed in green space and naturalness. However, to what extent can perceived naturalness influence students’ positive emotion remains unclear, especially in the context of COVID-19 countermeasures. This study, therefore, attempts to investigate in-depth the nature and strength of the relationships between students’ positive emotion and their perceived naturalness, place attachment and landscape preference, which are potentially varying across universities in different social and environmental contexts and different restriction policies regarding the COVID-19 pandemic. A course of questionnaire-based surveys was administered in two university campuses in Heilongjiang and Hunan Provinces, China, resulting in 474 effective samples. Structural equation modeling was used to explore the hypothetical conceptual framework of latent variables and the indicators. The findings indicate that the higher students’ perceived naturalness results in the greater positive emotion. Students’ perceived naturalness in green spaces of campus has a positive effect on their place attachment and landscape preference. Moreover, the difference of mediate effects of place attachment and landscape preference were addressed which verifies the contextual influences.